2023
DOI: 10.3390/su15021205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Dynamic Characteristics of Frozen Silty Clay and Its Influencing Factors

Abstract: Frozen soils are widely distributed in the seismically active regions of northwest China. Under the background of global warming, the study of the dynamic characteristics of frozen soil is very significant for the sustainable development of engineering in cold regions. In this study, the silty clay in the Lanzhou area of northwest China is selected to investigate the dynamic characteristics and its influence factors by dynamic triaxial tests. Various influence factors were considered, including confining press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Xu Feng [3] carried out finite element simulation on the soil of the canal base by filling, and the results showed that before and after filling, the lateral displacement of the trench was smaller than the change of lateral displacement when it was not filled. Li Haiyin [4] analyzed that before the soil moisture content reaches the saturated water content, the freezing rate of soil increases by 0.28% for every 1% increase in water content, and the freezing rate of soil increases by 0.17% for every 1°C decrease in temperature. Li Bin [5] showed through numerical simulation results that backfilling with sand and gravel materials can effectively inhibit the freezing antermate and reduce the freezing force.…”
Section: Introductionmentioning
confidence: 99%
“…Xu Feng [3] carried out finite element simulation on the soil of the canal base by filling, and the results showed that before and after filling, the lateral displacement of the trench was smaller than the change of lateral displacement when it was not filled. Li Haiyin [4] analyzed that before the soil moisture content reaches the saturated water content, the freezing rate of soil increases by 0.28% for every 1% increase in water content, and the freezing rate of soil increases by 0.17% for every 1°C decrease in temperature. Li Bin [5] showed through numerical simulation results that backfilling with sand and gravel materials can effectively inhibit the freezing antermate and reduce the freezing force.…”
Section: Introductionmentioning
confidence: 99%